The Impact of Service Quality Towards Customer Satisfaction in Selected Samgyeopsal Restaurants in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Many Filipinos are going crazy about it because of its unique concept of having various sidedishes, as Samgyeopsal has become popular in the Philippines. Service quality and customersatisfaction are important aspects of the business since a company’s growth is largelydependent on how well it maintains its customers through service and how well it keeps itscustomers satisfied. This study aims to investigate the impact of service quality on customersatisfaction for selected Samgyeopsal Restaurant in Quezon City".In terms of serving orders on the table, respondents have a minor problem when it comes tothe condition of tools and equipment. The respondents have a minor problem with theinstructions they give to employees. In other words, the employee did not understand theinstructions well given to them by the customer. The respondents had a minor problem withthe attention to their complaints. There are times that the customers do not get the attentionwell when they have some complaints.A recommendation for the service provider would be to focus on improving the conditions oftools and equipment to ensure that they are in good working condition and clean. Therestaurant could consider implementing strategies to address any areas that were identifiedas opportunities for improvement, such as increased attention to customer complaints.Continue to monitor customer feedback, identify areas for improvement in their customerservice processes, and maintain and improve customer satisfaction levels. SelectedSamgyeopsal Restaurant should focus on improving the minor problems identified by therespondents, particularly in the areas of tools and equipment condition, instructions given toemployees, and attention to customer complaints.
Keywords: Hospitality Management